Convergence in GDP per Capita in the Euro Area and the EU at the Time of COVID-19 - Mirko Licchetta; Giovanni Mattozzi (Intereconomics, 2023)
This paper investigates determinants of convergence in GDP per capita in the euro area and the EU between 1995 and 2021. It finds that the COVID-19 crisis temporarily slowed convergence but the estimated negative impact is significantly smaller than during the global financial crisis. Diverging effects emerged linked to the timing of the pandemic, the tightness of lockdown measures and the importance of contact-intensive sectors in the economy, like tourism. However, the easing of lockdown measures coupled with policy support (including the successful vaccination strategy) mitigated the risks of a pandemic-driven persistent divergence in growth. Regression results provide further evidence of convergence in the euro area and the EU over the period 1995-2021 and highlight the slowdown in convergence since the global financial crisis, which can be mostly attributed both to a contraction in investment rates in converging countries and to the limited catch-up in total factor productivity growth, especially in euro area countries.
Keywords: F00; O47; O52; 330; national income; economic convergence; epidemic; euro zone; EU countries; Nationaleinkommen; Wirtschaftliche Konvergenz; Epidemie; Eurozone; EU-Staaten